Experimental insights into factors influencing Vp/Vs ratios at the Nevado del Ruiz Volcano, Colombia - Aguilera Bustos, Joaquin Pablo; Adam, Ludmila (Volcanica, 2023)
Measurements of ultrasonic elastic waves were carried out at atmospheric and in-situ pressure conditions on rock samples from Nevado del Ruiz Volcano (NRV). The study focuses on Vp/Vs as a function of Vp as indicators of mineralogy, porosity, fluid-types and anisotropy. We find that Vp/Vs can separate the effect of microcracks vs. vesicles as a function of fluid type and effective pressures. Little-to-no pressure dependence in Vp/Vs suggest that the rock porosity is mainly comprised by vesicles, while largely varying Vp/Vs vs Vp is associated to cracks. This effect occurs under both, dry and fluid saturation conditions. When cracks close, the Vp/Vs values are representative of the rock mineralogy. Finally, as foliation results in a wide range of Vp/Vs, which could lead to misinterpretations. For instance, on NRV foliated rocks, Vp/Vs at dry conditions and parallel to the foliation plane ranges at values which are commonly associated to fluid saturation.